Order and delivery times simulation - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
It is clearly known that one of the big problems of production companies is not to deliver orders on time. When it happens, companies would have to pay a penalty fee and lose their reliability and so their customers. For that reason, companies have to have good plans or schedules about receiving and delivering times of orders. In this work, as a case study, simulation program of order and delivery times of a computer company where ordered computers are constructed according to costumer preferences and delivered to costumers by the via of cargo is described and simulation model is shown with an example. In this way, it is shown that with a simple simulation program, companies can solve their big problems effectively on order and deliver times.
Keywords: order; delivery time; simulation; modeling; PERMISSIBLE DELAY; INVENTORY MODEL; PAYMENTS; QUANTITY; DEMAND